2019
DOI: 10.1111/1442-1984.12229
|View full text |Cite
|
Sign up to set email alerts
|

Heritabilities of lateral and vertical herkogamy in Lysimachia arvensis

Abstract: Herkogamy, spatial separation between stigma and anthers within a flower, is important in regulating plant‐mating systems. We studied phenotypic variation and heritability of herkogamy traits in Lysimachia arvensis (=Anagallis arvensis) that show both lateral and vertical herkogamy in the same flower, a rare strategy in flowering plants. Both lateral and vertical herkogamy showed continuous variation in 15 natural populations. Lateral herkogamy, measured as the angle between style and stamens, ranged from 5.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Genetic differentiation between color morphs strongly suggests that gene flow between them is restricted, being to some extent reproductively isolated. This is also supported by other results found in previous studies and in other previous papers: niche differentiation with the blue-flowered plants more adapted to dry habitats (Arista et al, 2013), differences in flowering phenology found here and in a previous study (Arista et al, 2013) that hinder pollen flow between morphs at least partially, pollinator visitation in polymorphic populations where bees show floral constancy and prefer blue-flowered plants (Ortiz et al, 2015;Jiménez-López et al, 2020a), differences in inbreeding depression and mating system (in this study), and the low frequency of intermediate phenotypes in polymorphic populations (Jiménez-López et al, 2019a;2020b). These facts clearly indicate a history of gene flow limitation between morphs, suggesting they are different lineages.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Genetic differentiation between color morphs strongly suggests that gene flow between them is restricted, being to some extent reproductively isolated. This is also supported by other results found in previous studies and in other previous papers: niche differentiation with the blue-flowered plants more adapted to dry habitats (Arista et al, 2013), differences in flowering phenology found here and in a previous study (Arista et al, 2013) that hinder pollen flow between morphs at least partially, pollinator visitation in polymorphic populations where bees show floral constancy and prefer blue-flowered plants (Ortiz et al, 2015;Jiménez-López et al, 2020a), differences in inbreeding depression and mating system (in this study), and the low frequency of intermediate phenotypes in polymorphic populations (Jiménez-López et al, 2019a;2020b). These facts clearly indicate a history of gene flow limitation between morphs, suggesting they are different lineages.…”
Section: Discussionsupporting
confidence: 79%
“…No information about pollinator visitation in non-Mediterranean areas exists. Flowers of both colors show herkogamy (Jiménez-López et al, 2019a), but they open and close during 3 days and can self-pollinate during their lifespan, allowing reproductive assurance if outcross pollination fails.…”
Section: Introductionmentioning
confidence: 99%
“…We found 38 genes with significant differential expression between flower colors of L. arvensis across 94 genes in the flavonoid biosynthetic pathway. Our two sampled populations are geographically separated and may represent incipient species based on recent phylogenetic results ( Jiménez-López, 2019 ; Jiménez-López et al, in review ), which may have introduced some differences between the populations not correlated with color. Nevertheless, we still detected patterns correlated with color that are consistent with known functions of the ABP loci and previous studies of comparable flower color transitions.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why blue-flowered individuals have higher fitness in xeric and high temperatures compared to orange-flowered individuals. Flower life-span is also longer in blue flowers, as every day they open earlier and close latter than orange flowers ( Jiménez-López, 2019 ). Whether this is due to the different anthocyanins in the petals or pleiotropic effects in vegetative tissues is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation